Optimizing production in machining of hardened steels using response surface methodology - Campos, Paulo Henrique da Silva; Paes, Vinicius de Carvalho; Gonçalves, Ernany Daniel de Carvalho; Ferreira, João Roberto; Balestrassi, Pedro Paulo; Silva, João Paulo Davim Tavares da (Acta Scientiarum. Technology, 2019)
This paper presents the modeling of tool life and surface roughness for machining AISI 52100 steel with a hardness of 50 HRC through Design of Experiments and Response Surface Methodology (RSM) with a view to enhance the quality and productivity. Knowing that the tool life and surface roughness are factors that influence the quality of the product, this study used the statistical tool of RSM in the search of factors that better determine optimal models. The models obtained prioritize the product quality and the cutting productivity. Results from Analysis of Variance demonstrated that the mathematical models elaborated allowed the prediction of surface roughness parameters´ values and tool life (T) with a precision of 95% confidence interval and a coefficient of determination above 94%. The wiper geometry of the tool led to the achievement of low average surface roughness (Ra) ranging from 0.2 to 0.4 Âµm with relatively high advances (0.2-0.4 mm rev-1) and maximum height of the profile surface roughness (Rt) in the range of 1.4 to 2.8 Âµm, without making use of the cutting fluid.